2011
DOI: 10.1515/bc.2011.095
|View full text |Cite
|
Sign up to set email alerts
|

Fever-like temperature modification differentially affects in vitro signaling of bradykinin B1 and B2 receptors

Abstract: The bradykinin (BK) B 2 and B 1 receptors (B 2 R, B 1 R) belong to the rhodopsin-like G protein-coupled receptors (GPCRs) and are involved in (patho)physiological processes such as blood pressure regulation or inflammation. They mediate the effects of the pro-inflammatory peptides bradykinin/kallidin and desArg 9 -BK/desArg 10 -kallidin, respectively. Whereas the B 2 R is constitutively expressed and gets internalized upon activation, the B 1 R is especially induced by inflammatory mediators and responds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Texel and Mattson [ 53 ] reported that excess amyloid β fibril formation perturbed calcium homeostasis in mouse neuronal cells, possibly triggering apoptosis from calcium overload. BDKRB1 encodes for a bradykinin receptor that belongs to the rhodopsin-like GPRs that function in the regulation of inflammation [ 54 ]. The activation of BDKRB1 increases cytosolic calcium levels [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Texel and Mattson [ 53 ] reported that excess amyloid β fibril formation perturbed calcium homeostasis in mouse neuronal cells, possibly triggering apoptosis from calcium overload. BDKRB1 encodes for a bradykinin receptor that belongs to the rhodopsin-like GPRs that function in the regulation of inflammation [ 54 ]. The activation of BDKRB1 increases cytosolic calcium levels [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Increases in intracellular cAMP levels, often observed after addition of BK, are, almost exclusively, caused indirectly through stimulation of G s -coupled prostaglandin receptors. Activation of kinin receptors also results in the stimulation of mitogen-activated protein kinases (MAPK) cascades, with coupling to G-proteins G q/11 and G i/o being required for efficient stimulation of the ERK1/2 MAPK pathway by both B 2 R and B 1 R (Calixto et al, 2004;Leschner et al, 2011).…”
Section: Kinin Receptor Signalingmentioning
confidence: 99%
“…Although PGE 2 is fundamental in the febrile response, some cytokines and other inflammatory mediators may activate fever independent of PGE 2 [44]. Other than PGE 2 , inflammatory mediators that may disrupt thermal balance include bradykinin [45], corticotropin releasing hormone [46], nitric oxide [47], macrophage inflammatory protein1 (MIP-1) [48], endothelin [49], preformed pyrogenic factors (PFPF), and substance P [6,44]. The pyrogenic signal that is generated as a result of peripheral inflammatory challenge is likely transmitted to the brain where responses can be generated to cause a rise in body temperature [43].…”
Section: Fever Induction and Antipyresismentioning
confidence: 99%